Egy gyakorlat létrejötte és hatásmechanizmusa - Júlia Gyéresi (Symbolon)
The Creation and Mechanism of an Exercise Interactive media platforms offer a deluge of digital content, with providers eagerly watching how consumers become addicted to the latest and most interesting ideas. The mind no longer wanders freely, but rather receives images ready-made. The increasingly powerful impulses push those who are completely absorbed by anxiety-fueled constant alertness to the brink of mental exhaustion. This manipulative digital world prompted me to create an exercise that helps restore the vivid wiring of both hemispheres of the brain, generating internal images, activating vocabulary, while giving space for free associations, and placing verbal expressiveness to the forefront. I was able to measure the practical benefit of the exercise called “Themes and collective concepts” during its application. This exercise creates a simultaneous combination of imagination, mental lexicon, and verbal linguistic presence, and is an excellent opportunity for university students to achieve internal calm and be better able to focus.